PENGARUH JENIS PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS JAGUNG MANIS (Zea mays saccharata Sturt) - Ningsih, Nining Dwi; Marlina, Neni; Hawayanti, Erni (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2015)
Effect of organic fertilizer type on growth and production of several varieties of sweet corn (Zea mays saccharata Sturt). This study aims to identify and determine the type of fertilizer best organic effect on the growth and production of several varieties of sweet corn. This research has been carried out in experimental campus garden land C Muhammadiyah University of Palembang. Semambu Island Village District of North Indralaya, Ogan Ilir, South Sumaetra Province, from May to July 2015 and use design plots Divided (Split-plot design) with 12 combined treatment and repeated 3 times, namely the Main plot treatments Sweet Corn Varieties (V)= consist of V1= Sweet boy, V2= Osse, V3= Bonanza and children Petak ie Treatment Organic fertilizer cow dung, O3= Compos palm empty fruit bunches, O4= Compost LCC. The parameters observed plant height (cm), number of leaves (pieces), ear length (cm), cob diameter (cm), weight ear cropping (g), berangkasan dry weight (g), yield per hectare (kg). The result showed treatment varieties very significant effect on all observed variables. Treatment of organic fertilizer very significant effect on the cob length, cob diameter, cob weight and dry weight per plot berangkasan, but take effect no significant effect on plant height, number of leaves and cobs heavy cropping. Treatment interaction effect was not significant on all observed variables.